Menganalisis Formulasi Mashlahah Bagi Produsen: (Studi kasus Koperasi Berbasis Syariah SADIKA SMKS Saka Medika) - Cucu Rohendi; Nurul wulandari putri (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The birth of various Islamic financial institutions (LKS) shows that Islamic teachings cover the economic scope, including cooperatives in the form of Islamic finance These Islamic teachings must absolutely be obeyed and guided by all Muslims in making daily life activities, including in transaction and investment activities, Mashlahah refers to all forms of benefits or goodness that can bring prosperity to individuals and society in general. without ignoring sharia values. For manufacturers of mashlahah formulations, it is an important challenge in carrying out production activities that not only pursue material profits, but also contribute to economic sustainability, social justice, and environmental preservation Qualitative descriptive research is aimed at describing and describing existing phenomena, both natural and man-made, that pay more attention to the characteristics, quality, and linkages between activities. In addition, descriptive research does not provide treatment, manipulation or alteration to the variables studied, but rather describes a condition as it is. The only treatment given is the research itself, which is carried out through observation, interviews from competent sources in their fields The imbalance between profits and benefits is one of the fundamental issues in the formulation of mashlahah for producers who are faced with pressure to maximize profits in a short time, which sometimes has the potential to sacrifice the principles of benefits caused by several factors, such as adopting strategies that are oriented towards short-term profits to meet financial targets or pressure from shareholders. As a result, the benefits are often overlooked. The imbalance between profits and benefits is an important problem for sharia-based cooperatives that lack understanding of the principles of mashlahah in Islamic business, such as avoiding riba and using a clear profit-sharing system on every transaction